The Effect Of Self-Efficacy And Heart Communication On Recovery Motivation In Cancer Patients - Rima Maryani; Puji Lestari; Priyahita Garmadyuti Suryawijaya (Universitas Multimedia Nusantara, 2025)
Cancer is a disease with a high mortality rate in the world, including in Indonesia. Recovery motivation is an essential factor in the healing process of cancer patients, and various psychological aspects, including self-efficacy and heart communication, influence it. This study aims to analyze the effect of self-efficacy and heart communication on the recovery motivation of cancer patients at the Indonesian Cancer Foundation, Yogyakarta Special Region Branch (YKI DIY). The research method used is quantitative with a correlational survey. The research sample consisted of 55 cancer patients determined using a simple random sampling technique. Data were collected through a questionnaire measuring self-efficacy, heart communication, and recovery motivation. Data analysis used multiple linear regression tests to identify the influence between variables. The results showed that self-efficacy and heart communication significantly affected recovery motivation (R² = 71.8%). However, partially, only heart communication had a significant effect on motivation to recover (t count = 7.843; p <0.001), while self-efficacy did not show a significant impact (t count = 0.663; p> 0.05). These findings indicate that heart communication, with the dimensions of thought processing, feeling processing, managing heart trash, sympathy, empathy, peace, and happiness, is dominant in increasing recovery motivation in cancer patients.